NOx Emission Trading in a European Context: Discussion of the Economic, Legal, and Cultural Aspects - Chris P.A. Dekkers (The Scientific World Journal)
Emission trading is a new instrument in environmental policy. It is an alien notion in most European countries and it is often viewed with hesitation. The paper discusses the economic, legal, and perhaps more importantly, the cultural aspects to consider when one tries to explore the prospects for trading emissions of NOX and other substances in Europe. Issues to be addressed are the present legal framework in Europe in relation to the national emission ceilings on NOX and other substances on the basis of relevant EU directives and UNECE protocols. The paper will discuss the extent to which the legal framework within the EU imposes constraints on the design of a national emission trading scheme, and what options are available to fit emission trading into that legislative structure. The NOX emission trading programme developed in the Netherlands will be used to demonstrate the various aspects in a European context.